Low-dose ketamine adjuvant treatment for refractory pain in children, adolescents and young adults with cancer: a pilot study. Issue Volume 12:Issue e5(2022) (31st May 2019) - Courade, Magali; Bertrand, Amandine; Guerrini-Rousseau, Lea; Pagnier, Anne; Levy, Dominique; Lervat, Cyril; Cojean, Nadine; Ribrault, Alice; Dugue, Sophie; Thouvenin, Sandrine; Piguet, Christophe; Schmitt, Claudine; et al.
Abstract : Objectives: Ketamine, an N -methyl-D-aspartate receptor antagonist, is effective at relieving adult cancer pain, although there have been very few reports to date regarding its use in children and in adolescents and young adults (AYA). This study assessed the efficacy, safety and opioid-sparing effects of low doses of ketamine added to opioid analgesics to alleviate persistent cancer pain. Methods: This prospective, multicentre, observational trial collected data regarding demographics, pain characteristics, pain score assessment within the first 48 hours of ketamine administration, tolerance and satisfaction from 38 patients aged 2–24 years prescribed with ketamine as an adjuvant antalgic for refractory cancer pain in 10 French paediatric oncology centres. Results: The mean visual analogue scale pain score decreased from 6.7 to 4.3 out of 10 (n=39, p<0.001) from day 1 to day 3 and by at least 2 points in 56% of the patients (n=22) 48 hours after initiation of ketamine. Nine patients experienced poor tolerance (≥2 side effects), all with infusion rates lower than 0.05 mg/kg/hour. None had limiting toxicities. An opioid-sparing effect was highlighted in four patients. Fifty-four per cent of the prescribers and 47% of the patients found the addition of ketamine 'very helpful'. Conclusions: Low doses of ketamine as an adjuvant to opioids significantly reduced the intensity of pain in half of the study population. A tendency towards better pain control is shown, although a lack of statistical power somewhat limits our conclusions, especially in children. Nevertheless, ketamine may be a useful option for improving the treatment of refractory pain in children and AYA with cancer.